Environmental thermal actions - thermal analysis of Alto-Lindoso dam - Leitão, N. S. (2012)
In this work the finite element implementation of thermal analysis of concrete dams is described. The different temperature boundary conditions are properly represented. For the exposed face of the dam both convection/radiation heat transfer and solar radiation are implemented. The model is validated by calculating the response of a concrete arch dam and comparing the results of the monitoring system values.